Millimeter-Wave Reflectometry for Detecting Graphite Contamination in Titanium (Ti64) Powder Used in Additive Manufacturing (AM) - Jayaram Kizhekke Pakkathillam; Jessica Haack; Reza Zoughi (IEEE Open Journal of Instrumentation and Measurement, 2025)
Titanium (Ti64) alloys are extensively used for additive manufacturing (AM) of complex and critical parts in the aerospace industry. Titanium powder particle size, shape, and presence of satellites (in case of recycled powder) are important Ti64 feedstock powder quality indicators. In this investigation, millimeter-wave characterization of Ti64 alloy and graphite powders was performed by studying the reflection coefficient response of the powder samples using a circular waveguide probe (an open cavity) operating in axially symmetric mode (TE0m) at Ka-band (32–40 GHz) and Q-band (42–50 GHz) frequency ranges. In addition to Ti64 and graphite powders, graphite-contaminated Ti64 samples, containing different amounts of graphite powder, were prepared and measured. The primary objective of this work has been to evaluate the efficacy of millimeter-wave reflectometry, and the capability of this measurement technique, for distinguishing among different contaminated Ti64 powder samples with low levels of contamination (by weight). The contamination levels ranged from 0.0015% to 5% (graphite percentage of Ti64 weight). Measurements were carried out at different powder (cavity) depths to determine the optimum sample holder depth for the increased measurement sensitivity. It is reported that a 0.05% (by weight) level of carbon contamination in powder feedstock can lead to defects in the final printed part. Crucially, the results of this investigation showed that graphite contamination levels as low as 0.0045% (percentage by weight) can be robustly detected by this method.